Modeling Student Loyalty in Higher Education: Service Quality, Satisfaction, and University Image Effects - Egi Andiyana; Adesta Dwi Fajri; Andrean Eko Haryoko; Satrias Djamaran (Universitas Muhammadiyah Pontianak, 2026)
This study examines how service quality influences student satisfaction and its implications for student loyalty and university image in private higher education institutions in Tangerang Regency. Using a quantitative approach, data were collected from 197 students and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings show that non-academic aspects, program design, facilities, and industry interaction significantly influence student satisfaction, whereas the academic aspect is not significant. Student satisfaction strongly affects student loyalty and contributes to university image. These results imply that universities should enhance comprehensive service quality, particularly non-academic services and industry engagement, to strengthen student satisfaction, institutional reputation, and long-term student loyalty.